Fetal ascites and hydrometrocolpos due to persistent urogenital sinus and cloaca: a rare congenital anomaly and review of literature. (19th February 2014) - Nigam, Aruna; Kumar, Manisha; Gulati, Shilpa
Abstract : Fetal ascites can occur due to many heterogeneous disorders. Its association with hydrometrocolpos because of persistent urogenital sinus and cloaca is extremely rare. A 29-year-old primigravida presented at 32 weeks of gestation with ultrasonographic evidence of fetal ascites, a cystic pelvic mass, hydronephrosis and oligohydramnios. Fetal ascites in this case was due to fetal urine draining through fallopian tubes into the abdomen as a result of vesicovaginal fistula and distal vaginal atresia. The antenatal ultrasound results along with autopsy findings are discussed. Though rare, a persistent urogenital sinus is to be suspected in isolated fetal ascites cases where the viral tests are negative and there is no evidence of cardiac anomalies as this is a treatable anomaly if diagnosed at early gestational age.